Simple preparation method for Styrofoam-TiO2composites and their photocatalytic application for dye oxidation and Cr(vi) reduction in industrial wastewater - Lee, Youn Jun; Lee, Chang Gu; Kang, Jin Kyu; Park, Seong Jik; Alvarez, Pedro J.J. (Environmental Science: Water Research and Technology, 2021)
This study investigates a simple method for the preparation of floating photocatalysts in which the surface of expanded polystyrene (EPS) is partially dissolved using a diluted solvent that contains TiO2 particles. The acetone volume content (v/v) and TiO2 weight content (w/v) of the diluted solvent and the stirring time of the diluted solvent and EPS were optimized through methylene blue (MB) oxidation experiments. The surface morphology, TiO2 weight ratio, and functional group of the EPS-TiO2 composite (TiEPS) were characterized. Ethyl acetate, benzene, and acetone were selected as suitable solvents for dilution using this simple preparation method. MB degradation efficiency of the TiEPS remained stable over 20 reuse cycles, and minimal TiO2 leaching was observed (up to 3.6 μg L-1 of titanium). Photocatalytic reduction of Cr(vi) in wastewater from a plating plant was evaluated via a composite prepared using waste expanded polystyrene (W-TiEPS). More than 99% of the Cr(vi) was reduced to Cr(iii) within 75 min by W-TiEPS amended with citric acid under UV-A irradiation (λmax = 350 nm, 3.93 × 10-9 einstein per cm2 s-1). These results suggest that the floating photocatalyst produced via this simple and scalable method should be considered to remove Cr(vi) and perhaps other water and wastewater contaminants.
Keywords: Degradation efficiency; Ethyl acetates; Expanded polystyrene; Industrial wastewaters; Photocatalytic application; Preparation method; Scalable methods; Water and wastewater